Rhetorical, Metacognitive, and Cognitive Strategies in Teacher Candidates' Essay Writing - Claudio Díaz Larenas; Lucía Ramos Leiva; Mabel Ortiz Navarrete (Universidad Nacional de Colombia, 2017)
This paper reports on a study about the rhetoric, metacognitive, and cognitive strategies pre-service teachers use before and after a process-based writing intervention when completing an argumentative essay. The data were collected through two think-aloud protocols while 21 Chilean English as a foreign language pre-service teachers completed an essay task. The findings show that strategies such as summarizing, reaffirming, and selecting ideas were only evidenced during the post intervention essay, without the use of communication and socio-affective strategies in either of the two essays. All in all, a process-based writing intervention does not only influence the number of times a strategy is used, but also the number of students who employs strategies when writing an essay-two key considerations for the devising of any writing program.